SIKAP AL-QUR’AN TERHADAP YAHUDI: (Jawaban Atas Tuduhan Terhadap Al-Qur’an Anti-Semitis) - Muhammad Maghfur Amin (Institut Agama Islam Negeri (IAIN) Keiri, 2020)
This paper is a response to an issue exhaled by Ariel Muzicant about al-Qur'an anti-Semitic accusations. The issue is the writing of the Vice President of the European Jewish Congress, Ariel Muzicant, which is contained in a recent paper entitled